Activation energy, viscosity and fragility of Cu–Zr–Ti–In bulk metallic glasses. (May 2014) - Wu, J.; Pan, Y.; Liu, H.; Pi, J.
Abstract : In the present paper, activation energy, viscosity and fragility of two In alloyed Cu–Zr–Ti–In bulk metallic glasses are evaluated by differential scanning calorimetry and thermomechanical analysis respectively. E g of 60Cu–34Zr–5Ti–1In and 58Cu–34Zr–5Ti–3In is 175±9 and 182±5 kJ mol −1 respectively. E x of 60Cu–34Zr–5Ti–1In and 58Cu–34Zr–5Ti–3In is 369±24 and 317±10 kJ mol −1 respectively, indicating that increasing the content of indium decreases the value of E x of the as cast bulk metallic glasses. By means of comparison of activation energies referring to the crystallisation peak temperature, one can find that the second step crystallisation of both bulk metallic glasses is easier to occur. The possible phases of the annealed samples are determined. Thermomechanical analysis shows that viscosity for 58Cu–34Zr–5Ti–3In is larger than that for 60Cu–34Zr–5Ti–1In in the supercooled region, but Vogel–Fulcher–Tammann (VFT) temperature of 58Cu–34Zr–5Ti–3In is lower than that of 60Cu–34Zr–5Ti–1In. Both 60Cu–34Zr–5Ti–1In and 58Cu–34Zr–5Ti–3In bulk metallic glasses are stronger than o-terphenyl, but more fragile than SiO2 . 58Cu–34Zr–5Ti–3In is stronger than 60Cu–34Zr–5Ti–1In. It indicates that increasing indium content can decrease the VFT temperature but make glass stronger.